2023
DOI: 10.1037/ccp0000810
|View full text |Cite
|
Sign up to set email alerts
|

Early intervention for families experiencing homelessness: A pilot randomized trial comparing two parenting programs.

Abstract: Objective: As part of a larger community-based, service-driven research project, the primary purpose of this pilot randomized study was to examine the feasibility and acceptability of delivering time-limited adaptations of parent-child interaction therapy (PCIT) and child-parent psychotherapy (CPP) within a sample of children experiencing homelessness. The secondary goal was to examine the promise of both interventions in improving parent/child outcomes. Method: One hundred forty-four young children (18 month-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Both completers and non-completers reported high levels of satisfaction at mid-treatment, and at post-treatment, completers continued to report high levels of satisfaction. Women who participated in Parent–child interaction therapy (PCIT) and Child–parent psychotherapy (CPP) [ 80 ] reported high levels of overall satisfaction across both interventions noting greatest improvements in their parent–child relationship, feeling like their child made progress in terms of their general behaviour, progress related to their trauma symptoms or traumatic/stressful experiences, and generally positive feelings about the parenting programs. Over 90% indicated that they would likely recommend both programmes to others.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both completers and non-completers reported high levels of satisfaction at mid-treatment, and at post-treatment, completers continued to report high levels of satisfaction. Women who participated in Parent–child interaction therapy (PCIT) and Child–parent psychotherapy (CPP) [ 80 ] reported high levels of overall satisfaction across both interventions noting greatest improvements in their parent–child relationship, feeling like their child made progress in terms of their general behaviour, progress related to their trauma symptoms or traumatic/stressful experiences, and generally positive feelings about the parenting programs. Over 90% indicated that they would likely recommend both programmes to others.…”
Section: Resultsmentioning
confidence: 99%
“…Parenting interventions resulted in an improvement in psychological symptoms relative to baseline in two studies, and deterioration of symptoms in another study [ 71 , 72 , 80 ]. There is a small body of literature evaluating parenting interventions in homeless populations, most studies are methodologically weak, and outcomes generally relate to child behaviour and parenting skills, as opposed to parental mental health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations